Rancang Bangun Flow Meter Trainer Kit di Politeknik Negeri Batam - Qoriatul Fitriyah; Muhammad Prihadi Eko Wahyudi (Politeknik Negeri Batam, 2021)
Flow Meter Trainer Kit is designed because of the limited associated laboratory equipment at Politeknik Negeri Batam. Flow Meter Trainer Kit is a measuring tool for fluid flow which is equipped with the addition of pressure in the form of visual aids. In general, the process of water flow begins with a full filling of water tanks and then the pump will work to flow the water through pipes, passing pressure meters and rotameters whose duty is to read the results of fluid flow discharge measurements while adjusting the amount of fluid flow. Furthermore, water will flow through the water flow sensor and back into the tank. The practicum module will be developed based on this trainer kit.